THE ROLE OF MOTIVATION, DISCIPLINE, AND JOB SATISFACTION ON THE PERFORMANCE OF SMPI AND SMAI EDUCATORS AT DAARUSSA’ADAH ISLAMIC BOARDING SCHOOL FOUNDATION, PESAWARAN REGENCY - Zaqiyah, Ulfa; Barusman, Andala Rama Putra; Dunan, Hendri (Journal of Management, Business and Social Sciences, 2024)
This study aims to examine the simultaneous influence of motivation, discipline, and job satisfaction on the performance of educators at SMPI and SMAI under the Daarussa’adah Foundation in Pesawaran Regency. The research employed a mixed-method approach, combining both quantitative and qualitative methods. The population of the study consisted of all 70 educators working at the foundation. The sampling technique used was saturated non-probability sampling, and the data were processed using SPSS Statistics 26. Data were collected through interviews and questionnaires, while multiple linear regression analysis was applied to assess the relationship between independent and dependent variables. The findings revealed that motivation, discipline, and job satisfaction each have a significant positive effect on educator performance when analyzed separately. Furthermore, when examined together, these three variables also collectively exhibit a significant positive impact on the performance of educators.